Optimizing novasomes: impact of oleic acid and co-surfactant ratio on posaconazole delivery: In vitro & Ex vivo pharmacokinetic study - Rukari, Tushar; Pingale, Prashant L; Upasani, Chandrashekhar D (Journal of Applied Pharmaceutical Research, 2024)
Background: Posaconazole, currently available as a solid oral dosage form, possesses erratic pharmacokinetics that complicate dosing regimens and increase the risk of adverse effects and drug interactions. Hence, innovative strategies, especially topical ones, are necessary to enhance the therapeutic profile and improve patient outcomes. Methodology: The regular 23 factorial design and the concentrations of Oleic acid: Span 80 (2:1) ratio, Cholesterol, and Tween 80 as independent variables were used for the formulation development. The preliminary effect was determined by dependent variables like vesicle size and entrapment efficiency; then the final optimized batch was loaded in 3 % w/w Carbopol gel. Result and Discussion: The optimized batch's vesicle size and entrapment efficiency were 193.34+14.84 nm and 90.03+0.11 %, respectively. These results were found statistically significant (ANOVA) in the trial version of Stat-Ease 360®. Other evaluation parameters like zeta potential and pH of all the formulations were also significant (p<0.005). Conclusion: The optimized batch (NF7), when loaded with gel (NF7G-3), showed sustained release of Posaconazole up to 7 h in an In vitro diffusion study facilitated 87.14±0.11 % release confirming non-Fickian or Anomalous diffusion, interpreted from Korsmeyer Peppas (KKP) model. With the results from In vitro and Ex vivo pharmacokinetic release, the Posaconazole-loaded NF7G-3 Novasomal gel can exhibit potential formulation for the topical treatment of fungal infections. It will help significantly mitigate the negative effects of Posaconazole.